A CRITICAL ANALYSIS OF MORPHOLOGICAL CHARACTERS OF PLANT SPECIES TAKEN AS RUDANTI - Neha, *Pundir; Naveen, Upadhyay (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda was introduced as a science of prevention and cure of various ailments. Aacharya attained this profound knowledge through hit and trial methods and experiments. They used various herbs for this purpose. Medicinal plants are the essence of Ayurveda and Ayurvedic treatments. Keeping in mind the characteristics of plant drugs nomenclature was done. Later researchers took classical references about morphology, pharmacology and synonyms as base for identification of plants. This article will bring in light the morphological characters of various plant species that comes in approximation to one of the most controversial plant i.e. Rudanti. This paper is an attempt to eliminate state of confusion on Rudanti and to establish new plant species that fulfill the classical morphological identification criteria as mentioned in Raj Nighantu. This article also encompasses the folklore knowledge of the plant species established through evaluation of modern texts. This information will further validate the target species. Hence this is concluded that Capparis moonii and Cressa cretica taken in the name of Rudanti are not classical Rudanti as they do not resemble morphological characters. Astragalus and Cicer species that resemble Rudanti classical description should be taken. This can further be revalidated by preclinical/clinical trials.